2001
DOI: 10.1007/978-3-662-04448-3_18
|View full text |Cite
|
Sign up to set email alerts
|

On Classifications of Fitness Functions

Abstract: It is well-known that evolutionary algorithms succeed to optimize some functions efficiently and fail for others. Therefore, one would like to classify fitness functions as more or less hard to optimize for evolutionary algorithms. The aim of this paper is to clarify limitations and possibilities for classifications of fitness functions from a theoretical point of view. We distinguish two different types of classifications, descriptive and analytical ones. We shortly discuss three widely known approaches, name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 19 publications
3
29
0
Order By: Relevance
“…As such, several complementary measures are necessary [10,95,135]. Second, ELA methods require a large sample to be precise [66,95,149]. The sample size grows exponentially with D; hence, ELA methods are imprecise in polynomial time [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, several complementary measures are necessary [10,95,135]. Second, ELA methods require a large sample to be precise [66,95,149]. The sample size grows exponentially with D; hence, ELA methods are imprecise in polynomial time [53].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in Section 3.2, data driven methods, know as ELA methods, are the only valid approach to measure the problem characteristics for BCOPs. ELA is an umbrella term for analytical, approximated and non-predictive methods [53,66,86,91,104] originally developed for combinatorial optimization problems [137]. For BCOPs, the existing methods are adaptations from their combinatorial counterparts [19,20,85,95,101,103,144,150], or purposely built for continuous spaces [19,83,91,98,120].…”
Section: Characteristics Space: Exploratory Landscape Analysis Methodsmentioning
confidence: 99%
“…It has also been shown that it does not reliably predict the difficulty of optimising the problem (Altenberg, 1997;Jansen, 2001;Kallel, 1998, 2000;Quick et al, 1998;Reeves, 1999).…”
Section: Original Formulationmentioning
confidence: 99%
“…The most prominent of these may be the fitness-distance correlation (FDC) [46]. However, further theoretical investigations of Jansen [44] and He et al [38] have largely found the existing measures unsuitable for predictive purposes, so watching out for new properties surely makes sense. Furthermore, in exploratory landscape analysis, one is especially interested in what can be achieved with only few evaluations of the problem, as the ultimate goal usually is to set up a good optimization algorithm for expensive problems with unknown properties.…”
Section: Important Problem Propertiesmentioning
confidence: 99%